Potential Impacts of PIT Tagging on a Critically Endangered Small‐Bodied Fish: A Trial on the Surrogate Mountain Galaxias. Issue 6 (6th September 2018) - Allan, Hugh; Unmack, Peter; Duncan, Richard P.; Lintermans, Mark
Abstract: Recent advances in PIT technology have led to smaller tags, meaning that this technology can be used to mark and monitor smaller‐bodied species, many of which are threatened. We examined the effects of 9‐mm PIT tags on the survival and growth of the Mountain Galaxias Galaxias olidus, using this fish as a surrogate for several threatened, small‐bodied galaxiids. We measured survival, growth, and tag retention in 34 tagged and 34 untagged fish held in aquaria for 90 d posttagging. Fish were randomly assigned to a treatment (tagged or untagged) and were weighed just prior to tagging and then at 7, 14, 21, 28, 42, and 90 d after tagging, with observations made 5–7 times per week to check for survival and tag loss. Survival did not differ significantly between tagged and untagged groups (79% and 88%, respectively), and there was no difference in weight gain or loss between the two groups over time. Tag retention rate was high (96%), with only one tag expelled by the smallest tagged fish (73 mm length to caudal fork). Our findings show that Mountain Galaxias are capable of successfully retaining 9‐mm PIT tags in aquarium conditions, suggesting that this technology is suitable for the monitoring of similar small‐bodied fish in the wild.